Penerapan Strategi Pemasaran Digital Bisnis Kuliner Rumahan Bagi Jemaat GKP Klasis Jakarta-Banten - Carolina F. Sembiring; Nenny Anggraini; Arya Gina Tarigan; Maria Yulan Christina; Virginia Poppi Panjaitan; Flora Ferdinanda Imoliana (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM), Univesitas Kristen Indonesia, 2025)
The bakery business, particularly dry cakes, has rapidly grown as part of the promising food and beverage industry, especially during significant religious events. To support this, the Economic Development Commission of the Church of the Christian Pasundan Synod of Jakarta and Banten is working to encourage the congregation’s economy and improve family income through the empowerment of small businesses (UMKM) in the dry cake sector, led by one of the congregation members, Mrs. Wenny Widiawati, with her business